Development and analysis of rGO‑MoS2 nanocomposite as top electrode for the application of inverted planar perovskite solar cells via SCAPS‑1D device simulation - Mohd Abid, Mohd Asyadi 'Azam; Safie, Nur Ezyanie; Md Sairi, Mohamad Nazmi Faiz; Takasaki, Akito (Springer Nature, 2022)
Due to the poor interface contact between perovskite and the noble metal electrode of perovskite solar cells (PSCs), the stability issues are undoubtedly critical. The main objective of this work is to analyze the workability of rGO-MoS2 nanocomposite as the top electrode. The rGO-MoS2 nanocomposite has been prepared experimentally via the refluxing method. The nanocomposite formation is confirmed via X-ray diffraction and Raman spectroscopy as the peaks of both materials found in the nanocomposites indicate a successive composite of the rGO-MoS2. The electrical properties of the sample are examined via a four-point probe. The lowest sheet resistance (10.7 Ω/sq) was obtained for the ratio rGO-MoS2 (5:5). The optical bandgap of the nanocomposite measured via UV–Vis spectroscopy also shows the narrowest bandgap (1.25 eV), which is ideal for photocatalytic application. The power conversion efficiency (PCE) of the solar cells shows remarkable results of 19.68%, confirming the compatibility of rGO-MoS2 electrode.